Aerosol-Jet-Printed Encapsulation of Organic Photovoltaics - Basu, Robin; Siah, Kok Siong; Distler, Andreas; Häußler, Felix; Franke, Jörg; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Organic electronic devices (OEDs) are prone to oxygen- and water-induced degradation and therefore need to be encapsulated with barrier materials. In this work, an aerosol jet (AJ)-printing process is developed to coat perhydropolysilazane (PHPS) directly onto OEDs by adapting the print setup and systematically optimizing the process parameters. Furthermore, a novel curing process that converts PHPS to silica barrier layers is developed by combining damp heat (DH) exposure with subsequent vacuum–UV irradiation. This two-step treatment is shown to be considerably faster and gentler than the state-of-the-art curing processes and also yields a quantitatively higher conversion. Both the printing and the conversion process are fully compatible with OED devices, which is demonstrated by a damage-free direct encapsulation of organic solar cells. The encapsulated cells show a significant reduction of degradation in DH conditions (65 °C/85% r.h.), maintaining >95% of their initial performance for >100 h. Complementary electroluminescence measurements reveal that the AJ-printed barrier layers effectively prevent lateral water ingress into the devices. Herein, the proof of principle is provided that AJ printing can be used to print barrier layers directly onto OEDs and is thus an industrially highly relevant technology to precisely encapsulate such devices even on 3D objects.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aerosol jet printing; organic solar cells; perhydropolysilazane; printed barriers; solution-processed encapsulation

A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

All inkjet-printed organic solar cells on 3D objects - Steinberger, Marc; Distler, Andreas; Hörber, Johannes; Tam, Kai Cheong; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
Drop-on-demand inkjet printing is a promising and commercially relevant technology for producing organic electronic devices of arbitrary shape on a wide variety of different substrates. In this work we transfer the inkjet printing process of organic photovoltaic devices from 2D to 3D substrates, using a 5-axis robot system equipped with a multi-nozzle inkjet printing unit. We present a ready-to-use 3D printing system for industrial application, using a 5-axis motion system controlled by commercial 3D motion software, combined with a commonly used multi-nozzle inkjet print head controlled by the corresponding printing software. The very first time inkjet-printed solar cells on glass/ITO with power conversion efficiencies (PCEs) of up to 7% are realized on a 3D object with surfaces tilted by angles of up to 60° against the horizontal direction. Undesired ink flow during deposition of the inkjet-printed layers was avoided by proper ink formulation. In order to be able to print organic (opto-)electronic devices also on substrates without sputtered indium tin oxide bottom electrode, the bottom electrode was inkjet-printed from silver nanoparticle (AgNP) ink, resulting in the first all inkjet-printed (i.e. including bottom electrode) solar cell on a 3D object ever with a record PCE of 2.5%. This work paves the way for functionalizing even complex objects, such as cars, mobile phones, or ‘Internet of Things’ applications with inkjet-printed (opto-)electronic devices.
CRIS-Team Scopus Importer:2024-07-05
Keywords: 3D functionalization; 3D printing; inkjet printing; organic solar cells; silver nanoparticles

All sub-nanosecond laser monolithic interconnection of OPV modules - Kubis, Peter; Winter, Jan; Gavrilova, Anna; Hennel, Markus; Schlosser, Susanne; Richter, Isabel; Distler, Andreas; Heyder, Madeleine; Kery, Stefan; Lenk, Peter; Geiger, Stephan; Brabec, Christoph; et al. (Progress in Photovoltaics, 2019)
Although green femtosecond lasers provide outstanding quality and wide processing windows for monolithic interconnection of the individual cells in organic photovoltaic (OPV) modules, they are hardly used in commercial applications, due to cost reasons. In this work, a process has been developed that allows the monolithic interconnection in OPV modules with an infrared sub‐nanosecond laser exclusively, without compromising the performance of the modules. While the photoactive layer is removed easily by green femtosecond pulses without damaging the bottom electrode, this is not possible for infrared nanosecond pulses, due to their much larger optical penetration length, which significantly exceeds the thickness of the active layer and is well absorbed by the indium tin oxide (ITO) layer. This leads to damage of the ITO bottom electrode, which in turn compromises the functionality of the module. By systematically varying single‐pulse laser fluence and spatial pulse overlap, the laser parameters are optimized in such a way that the contact area between the residues of the metal oxide bottom electrode and the silver nanowire top electrode is maximized so that the electrical resistances of the contacts are sufficiently small not to affect device performance. This is demonstrated by presenting large‐area OPV modules based on the well‐characterized reference system P3HT:PCBM that show efficiencies of up to 2.4%. This achievement opens up the way towards reliable roll‐to‐roll (R2R) laser patterning processes with sub‐nanosecond lasers and thus represents a breakthrough with respect to cost‐effective R2R manufacturing of OPV modules, due to grossly reduced investment and maintenance costs for laser sources.<br
Keywords: sub-nanosecond pulses; flexible organic photovoltaic module; laser patterning

A matter of design and coupling: high indoor charging efficiencies with organic solar modules directly coupled to a sodium ion battery - Kin, Li Chung; Distler, Andreas; Astakhov, Oleksandr; Kone, Bakary; Kungl, Hans; Karl, André; Merdzhanova, Tsvetelina; Eichel, Rüdiger A.; Brabec, Christoph; Rau, Uwe (Journal of Materials Chemistry A, 2024)
To tackle the challenge of powering distributed autonomous indoor sensors and electronics, such as in the implementation of the internet of things (IOT), a high-efficiency solar module with integrated storage is a potential solution that offers a stable, reliable power source. For this, organic photovoltaics (OPV) are a promising candidate, delivering high efficiencies under indoor lighting, flexibility, scalability and low-cost designs via roll-to-roll manufacturing. Pairing an OPV device with batteries made from widely available sodium seems to be a viable strategy for achieving a low-cost, low-power, self-charging power source. PV devices can be coupled directly to batteries without power conditioning. Self-sustained operation and stable power output of this power harvester are achievable with proper voltage matching and scaling of both the PV and battery within the target range of operating conditions. We achieved a record indoor direct charging overall efficiency of an OPV and sodium ion battery of 13.1-14.4% over a wide range of LED illumination intensities of 150-15 000 lx.
CRIS-Team Scopus Importer:2024-11-01

A Stage-Gate Framework for Upscaling of Single-Junction Perovskite Photovoltaics - Forberich, Karen; Albrecht, Steve; Castriotta, Luigi Angelo; Distler, Andreas; Hauch, Jens; Kirchartz, Thomas; Paetzold, Ulrich W.; Schorr, Susan; Sprau, Christian; Stannowski, Bernd; Ternes, Simon; Unger, Eva; et al. (Advanced Energy Materials, 2025)
To address the challenge of upscaling single-junction perovskite photovoltaics (PV) toward market-relevant performance in a structured and efficient manner, a stage-gate approach that divides the process into stages according to technology readiness levels (TRLs) is proposed. Whereas the first stage contains only material research, the later stages are concerned with the development from lab-scale devices to large-area modules, and properties such as device size as well as processing methods are adapted step-by-step toward commercializable techniques. The stages are connected by gates that specify the criteria that must be met for a material or process to be transferred to the next stage. In addition, a literature survey for the keywords “perovskite” and “module” is performed. This analysis shows that most of the reported modules have an area between 10 cm2 and 20 cm2, corresponding to stage 3 or TRL 5 in the scheme, and operational stability is often incompletely reported. These findings analysis indicate a significant gap in the research focus on large-area modules and elevated stress and field tests, which are essential for transitioning to commercial applications. It is suggested to use the proposed stage-gate process as an efficient and structured guideline toward commercializing perovskite PV.
CRIS-Team Scopus Importer:2025-02-04
Keywords: commercialization; large-area; module; perovskites; upscaling

Challenges and opportunities in upscaling inkjet-printing of OPV - Steinberger, Marc; Qingguang, Xie; Ronsin, Olivier J.J.; Maisch, Philipp; Tam, Kai Cheong; Distler, Andreas; Harting, Jens; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
The power conversion efficiency and long-term stability of organic solar cells have increased tremendously over the past years, reaching up to 19.2% on research cells and 14.5% on large modules. To take the final step towards industrialization, fabrication methods that can be upscaled and directly implemented in industrial processes need to be developed. In recent years, well-known industrial techniques, like drop-on-demand inkjet printing, have been further developed within the organic photovoltaics (OPV) community, as it enables versatile printing of arbitrary, free-form organic solar modules with different colors-a key feature for modern building-integrated photovoltaics and several niche applications of OPV printed on any kind object. In this review, aside a brief summary of recent developments, we provide an overview of the biggest challenges in OPV inkjet-printing and define design rules to overcome these issues. Further perspectives of OPV inkjet-printing conclude the review.
CRIS-Team Scopus Importer:2025-02-04
Keywords: inkjet-printing; organic photovoltaics; upscaling

CO2 snow jet cleaning as a roll-to-roll compatible method for deburring IMI substrates after laser patterning - Wagner, Michael; Distler, Andreas; Schmidt, Hans-Dieter; Classen, A.; Stubhan, T.; Koegl, M.; Illg, J.; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2023)
Burring is commonly encountered upon patterning of dielectric-metal-dielectric (DMD) transparent electrodes by laser ablation. These burrs are conductive and thus lead to shunting of the (opto-)electronic devices built upon these electrodes. In this work, CO2 snow jet blasting is presented as a convenient and reliable method for deburring laser-patterned DMD electrodes during roll-to-roll manufacturing of organic solar modules. As CO2 snow jet blasting significantly reduces the extent of shunting and concomitantly avoids scratching the electrode, the photoelectrical conversion efficiencies of the solar modules thus produced are higher than those obtained for traditional deburring techniques.
CRIS-Team Scopus Importer:2023-02-10
Keywords: carbon dioxide snow jet; deburring; laser patterning; printed photovoltaics; transparent electrode

Comparative analysis of outdoor energy harvest of organic and silicon solar modules for applications in BIPV systems - Feroze, Sarmad; Distler, Andreas; Forberich, Karen; Ahmed Channa, Iftikhar; Doll, Bernd; Brabec, Christoph; Egelhaaf, Hans-Joachim (Solar Energy, 2023)
Organic photovoltaics (OPV) have the potential to fill niches that traditional silicon photovoltaics (Si-PV) have left open so far. Building-integrated photovoltaics (BIPV) is one key area where OPV modules can play a vital role due to their functional attributes of semitransparency, flexibility, and lightweight. However, the architectural constraints and physical layout of buildings often do not allow the installation of photovoltaic (PV) modules at their optimal angles. Herein, we report the outdoor energy harvest of commercial OPV, and monocrystalline silicon (m-Si) modules mounted at inclinations of 45° and 90°, using the ISOS-O2 protocol as a test standard. The semitransparent OPV modules incorporating a P3HT:PCBM bulk heterojunction absorbing layer were found to offer daily specific energy yields (YF) that are 10–15% higher than those of the m-Si modules at 45° inclination. For vertical (90°) mounting, the YF of the OPV modules is even 24–30% higher than that of their inorganic counterparts, thus making them ideally suited for façade integrated BIPV. Laboratory investigations reveal that the superior performance of OPV modules in the vertical position is mainly due to a strongly enhanced fill factor (FF) at reduced in-plane irradiance. At a 45° inclination, the positive temperature coefficient of the OPV modules also plays an important role during high-irradiance hours.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Building-integrated photovoltaics; Energy harvest; Organic photovoltaics; Outdoor monitoring

Cutting “lab-to-fab” short: high throughput optimization and process assessment in roll-to-roll slot die coating of printed photovoltaics - Wagner, Michael; Distler, Andreas; Le Corre, Vincent Marc; Zapf, Simon; Baydar, Burak; Schmidt, Hans-Dieter; Heyder, Madeleine; Forberich, Karen; Lüer, Larry; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2023)
Commercialization of printed photovoltaics requires knowledge of the optimal composition and microstructure of the single layers, and the ability to control these properties over large areas under industrial conditions. While microstructure optimization can be readily achieved by lab scale methods, the transfer from laboratory scale to a pilot production line (“lab to fab”) is a slow and cumbersome process: first, the difficulty of operating structure-sensitive methods in-line impedes proper microstructure characterization, and second, the processing-functionality relationship must be redetermined for every material combination as the results obtained by typical lab-scale spin-coating cannot be directly transferred to other coating methods. Here, we show how we can optimize the performance of organic solar cells and at the same time assess process performance in a 2D combinatorial approach directly on an industrially relevant slot die coating line. This is enabled by a multi-nozzle slot die coating head allowing parameter variations along and across the web. This modification allows us to generate and analyze 3750 devices in a single coating run, varying the active layer donor : acceptor ratio and the thickness of the electron transport layer (ETL). We use Gaussian Process Regression (GPR) to exploit the whole dataset for precise determination of the optimal parameter combination. Performance-relevant features of the active layer morphology are inferred from UV-Vis absorption spectra. By mapping morphology in this way, small undesired gradients of process conditions (extrusion rates, annealing temperatures) are detected and their effect on device performance is quantified. The correlation between process parameters, morphology and performance obtained by GPR provides hints to the underlying physics, which are finally quantified by automated high-throughput drift-diffusion simulations. This leads to the conclusion that voltage losses which are observed for very thin ETL coatings are due to incomplete coverage of the electrode by the ETL, which causes enhanced surface recombination.
CRIS-Team Scopus Importer:2023-11-10

Effect of PCBM on the photodegradation kinetics of polymers for organic photovoltaics - Distler, Andreas; Kutka, Peter; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Guldi, Dirk Michael; Di Nuzzo, Daniele; Meskers, Stefan C. J.; Janssen, Rene A. J. (Chemistry of Materials, 2012)
The photo-oxidation behavior of three different polymers-namely, poly(3-hexylthiophene) (P3HT), poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2, 1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT), and poly[2,6-(4,4-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-alt- 4,7-(2,1,3-benzothiadiazole)] (Si-PCPDTBT)-is investigated in neat polymer films and in blends with [6,6]-phenyl-C-butyric acid methyl ester (PCBM) for different polymer:PCBM ratios. PCBM is shown to have both stabilizing and destabilizing effects, the extent of which is dependent on the type of polymer with which it is blended. Screening of the polymer from incident light by PCBM turns out to play an only minor role in the stabilization of P3HT. Quenching of the polymer excited states is also not a significant stabilization mechanism, as demonstrated by the comparison of the reduction of photo-oxidation rates to the extent of photoluminescence quenching by PCBM and 2,7-dinitrofluorenone (DNF). Photoinduced absorption spectroscopy reveals that the enhanced degradation of C-PCPDTBT in blend films with PCBM correlates with the population of the polymer triplet state via the polymer:PCBM charge-transfer state. © 2012 American Chemical Society.

Fassadenelemente mit organischer Photovoltaik - Egelhaaf, Hans-Joachim; Brabec, Christoph; Neberich, Marcel; Senguttuvan, Kaushik; Hoga, Felix; Kießling, Günther; Braun, Matthias; Bordin, Susanna; Wagner, Michael; Distler, Andreas; Feroze, Sarmad; Dentel, Arno (BWK Das Energie Fachmagazin, 2021)
In dem vom Bundesministerium für Wirtschaft und Energie (BMWi) geförderten Projekt „Fassade3“ entwickelt ein Konsortium aus akademischen und industriellen Partnern ein multifunktionales Fassadenelement mit integrierter organischer Photovoltaik (OPV). Die Fassade kann aufgrund ihrer modularen Struktur vorgefertigt und sowohl in Neu- als auch Bestandsgebäude integriert werden. Sie fungiert als Energiequelle, dient der thermischen Isolation, bietet Sonnenschutz für den Innenraum und optimiert so die Energieeffizienz des Gebäudes. Mit einfachen Mitteln lässt sich somit eine voll funktionsfähige und gleichzeitig ästhetisch ansprechende Konstruktion realisieren. Ein eigens entwickeltes Messsystem erlaubt die Echtzeit-Überwachung der Energiebilanz der Fassade. Erste Ergebnisse zum Leistungsverhältnis der OPV-Module sind vielversprechend.

Fully Printed and Industrially Scalable Semitransparent Organic Photovoltaic Modules: Navigating through Material and Processing Constraints - Wachsmuth, Josua; Distler, Andreas; Liu, Chao; Heumüller, Thomas; Liu, Yang; Aitchison, Catherine M.; Hauser, Alina; Rossier, Michael; Robitaille, Amélie; Llobel, Marc Antoine; Morin, Pierre Olivier; Thepaut, Anaïs; et al. (Solar RRL, 2023)
While the power conversion efficiency (PCE) of organic photovoltaics (OPV) on small-area lab cells has rapidly increased during the last few years, the performance on module level and the availability of OPV modules on the market is still limited, primarily due to specific constraints imposed by the industrial production process. This work deals with the upscaling process of latest-generation OPV from small-area lab cells to fully solution-processed modules, which are compatible to industrial roll-to-roll (R2R) printing. This transfer is demonstrated step by step from material selection and process optimization for every single layer of the stack (photoactive layer, charge transporting layers, and solution-processed top electrode)–including long-term stability investigations (thermal and light)–to scaling up the device area by a factor of >100. Thus, a semitransparent OPV module with 10.8% PCE on 10.2 cm2 active area is achieved, which is among the highest performances for semitransparent, fully solution-processed OPV modules. The individual developments all meet the requirements for industrial R2R printing (green solvents, processing in air, annealing ≤140 °C, etc.), which ensures that both the optimized layer stack and the fabrication process are fully scalable and easily transferable to large-scale production.
CRIS-Team Scopus Importer:2023-09-22
Keywords: ambient air; organic photovoltaics (OPVs); roll-to-roll (R2R)-compatibility; semitransparent modules; solution-processing; upscaling

Fully solution-processed, light-weight, and ultraflexible organic solar cells - Güler, Ezgi; Distler, Andreas; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2022)
Organic photovoltaic (OPV) devices have the potential to be superior to other PV technologies for the use in applications that require very high flexibility or maximum specific power (power-per-weight ratio), such as textile integration, wearable electronics, or outer space applications. However, OPV devices also require encapsulation by barrier films to reduce the degradation driven by extrinsic factors, which in turn limits their flexibility and leads to lower specific power values. In this work, fully solution-processed (including both electrodes) semitransparent organic solar cells (OSCs) with performance comparable with conventional indium tin oxide-based devices are processed directly onto different barrier films of varying thicknesses. Direct cell fabrication onto barrier films leads to the elimination of the additional polyethylene terephthalate substrate and one of the two adhesive layers in the final stack of an encapsulated OPV device by replacing the industrial state-of-the-art sandwich encapsulation with a top-only encapsulation process, which yields significantly thinner and lighter 'product-relevant' PV devices. In addition to the increase of the specific power to 0.38 W g(-1), which is more than four times higher than sandwich-encapsulated devices, these novel OSCs exhibit better flexibility and survive 5000 bending cycles with 4.5 mm bending radius. Moreover, the devices show comparable stability as conventionally encapsulated devices under constant illumination (1 sun) in ambient air for 1000 h. Finally, degradation under damp heat conditions (65 degrees C, 85% rh) was investigated and found to be determined by a combination of different factors, namely (UV) light soaking, intrinsic barrier properties, and potential damaging of the barriers during (laser) processing.
CRIS-Team WoS Importer:2022-05-13
Keywords: solution-processability; specific power; organic photovoltaics; silver nanowire; transparent electrodes; flexible electronics; barrier films

Improved Air Processability of Organic Photovoltaics Using a Stabilizing Antioxidant to Prevent Thermal Oxidation - Steinberger, Marc; Distler, Andreas; Brabec, Christoph J.; Egelhaaf, Hans-Joachim (Journal of Physical Chemistry C, 2021)
During the production of organic solar cells, the exposure of constituting materials and resulting devices to light, heat, oxygen, and water is a potential source of degradation. We show that thermo-oxidation of the active materials occurs upon annealing the active layer or upon stirring the active materials solutions in air at elevated temperatures. By comparing various blends of donor polymers with fullerene or nonfullerene acceptors, fullerene is identified to be the most susceptible component to thermal oxidation in both film and solution, while the polymer remains unaffected. In both cases, the effect on the photovoltaic device performance consists predominantly in a decreased short-circuit current (J(SC)), suggesting that the underlying degradation mechanism is the same in the solid state and in solution. In addition, we find that thermo-oxidation of the active layer during annealing of the device can be decelerated by blending nickel(II) dibutyldithiocarbamate (Ni(dtc)(2)) as an antioxidant additive into the active layer. While small concentrations of additive stabilize JSC and therefore the power conversion efficiency, higher contents negatively affect device performance. On the other hand, thermo-oxidation of the active materials in solution during stirring in air at elevated temperatures can be avoided for several hours by adding as little as 0.5% Ni(dtc)(2). The observation that the antioxidant is consumed during stabilization of the active materials suggests a sacrificial protection mechanism.
CRIS-Team WoS Importer:2022-01-14

Increased thermal stabilization of polymer photovoltaic cells with oligomeric PCBM - Ramanitra, Hasina H.; Dowland, Simon A.; Bregadiolli, Bruna A.; Salvador, Michael; Silva, Hugo Santos; Begue, Didier; Graeff, Carlos F. O.; Peisert, Heiko; Chasse, Thomas; Rajoelson, Sambatra; Osvet, Andres; Brabec, Christoph; et al. (Journal of Materials Chemistry C, 2016)
The first oligomerisation of phenyl-C-butyric acid methyl ester (PCBM) using a facile atom transfer radical addition polymerization (ATRAP) and its exploitation for organic photovoltaic devices is described. Oligo(phenyl-C-butyric acid methyl ester)-alt-[1,4-bis(bromomethyl)-2,5-bis(octyloxy)benzene] (OPCBMMB) shows opto-electronic properties equivalent to those of PCBM but has a higher glass transition temperature. When mixed with various band gap semiconducting polymers, OPCBMMB delivers performances similar to PCBM but with an enhanced stabilization of the bulk heterojunction in photovoltaic devices on plastic substrates under thermal stress, regardless of the degree of crystallinity of the polymer and without changing opto-electronic propertie
Keywords: Engineering controlled terms: Atom transfer radical polymerization; Electronic properties; Energy gap; Esters; Free radical reactions; Glass transition; Heterojunctions; Oligomers; Photoelectrochemical cells; Photovoltaic cells; Semiconducting polymers; Stabilization; Substrates Atom transfer radical addition; Bulk heterojunction; Degree of crystallinity; Optoelectronic properties; Organic photovoltaic devices; Photovoltaic devices; Polymer photovoltaic cells; Thermal stabilization Engineering main heading: Butyric acid

Influence of the fullerene LUMO level on the stability of bulk heterojunction solar cells - Distler, A.; Cheon, K. -S.; Waller, D.; Guldi, Dirk Michael; Hauch, J.; Egelhaaf, H. -J. (Journal of Materials Chemistry C, 2021)
Poly(3-hexylthiophene) (P3HT) is combined with a series of C-60-based derivatives with LUMO energies varying between -3.53 and -3.83 eV, in order to study the influence of the fullerene LUMO level on the performance and stability of organic solar cells as well as the degradation of the photoactive materials. UV/vis measurements show that P3HT degrades more slowly in all investigated P3HT:fullerene blends compared to neat P3HT films when being irradiated in air. Accordingly, all fullerene derivatives stabilize P3HT against photo-oxidation, albeit to different extents, with the electron affinity of the fullerene determining the degree of stabilization. A fullerene LUMO level of -3.75 eV is found to cause maximum stabilization, while the degradation rate increases for higher and lower values. Remarkably, the higher the stabilization effect imposed by the fullerene the slower the fullerene degrades itself, which indicates a non-sacrificial mode of stabilization. Transient absorption spectroscopy measurements show similar kinetics of exciton quenching and charge generation for all P3HT:fullerene combinations indicating a similar morphology in all blend films. Inverted solar cells made from the different P3HT:fullerene blends exhibit a good correlation between fullerene LUMO level and open-circuit voltage. Upon illumination in air, the photovoltaic devices follow the same degradation trend as the isolated photoactive layers by showing the same dependence on the fullerene LUMO level. Finally, we discuss different mechanisms, by which fullerene acceptors are potentially able to stabilize (UV light screening, excited-state quenching, and radical scavenging) as well as destabilize (morphological effects, superoxide or singlet oxygen sensitization, and polymer triplet-state population) donor polymers.
CRIS-Team WoS Importer:2021-07-23

Large-area organic photovoltaic modules with 14.5% certified world record efficiency - Basu, Robin; Gumpert, Fabian; Lohbreier, Jan; Morin, Pierre Olivier; Vohra, Varun; Liu, Yang; Zhou, Yinhua; Brabec, Christoph; Egelhaaf, Hans-Joachim; Distler, Andreas (Joule, 2024)
Organic photovoltaics (OPVs) have experienced a significant increase in power conversion efficiency (PCE) recently, now approaching 20% on small-cell level. Since the efficiencies on the module level are still substantially lower, focused upscaling research is necessary to reduce the gap between cells and modules. In this work, we present the upscaling of PM6:Y6-C12:PC61BM-based devices, processed in ambient air from non-halogenated solvents, from small-area cells to large-area modules with barely any performance loss. Supported by computational fluid dynamics simulations, an accelerated blade coating process that enables homogeneous coatings with <5% thickness deviation over 200 cm² is developed. Additional finite element method simulations are used to optimize the module layout and minimize the inevitable losses caused by electrode resistances and inactive interconnect areas to 1.9% and 3.5%, respectively. Finally, a 204-cm² OPV module with a certified PCE of 14.5% (15.0% on active area) is fabricated, which constitutes the new world record.
CRIS-Team Scopus Importer:2024-04-05
Keywords: certified world record efficiency; FEM simulations; laser patterning; OPVs; organic photovoltaics; process optimization; solar modules; solution-processed in ambient air

Long term outdoor performance evaluation of printed semitransparent organic photovoltaic modules for BIPV/BAPV applications - Feroze, Sarmad; Distler, Andreas; Dong, Lirong; Wagner, Michael; Channa, Iftikhar Ahmed; Hoga, Felix; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2024)
Recently, organic photovoltaics (OPV) have achieved power conversion efficiencies (PCE) above 20% thus coming closer to market entry. Building-integrated photovoltaics (BIPV) and building-attached photovoltaics (BAPV) are two key areas where the functional advantages of both OPV and BIPV/BAPV complement each other and thus could pave the way for market penetration of OPV. Herein, we report on large-area, all-solution-processed flexible OPV modules manufactured by a fully roll-to-roll (R2R) method with high levels of process repeatability. The OPV modules show an accelerated lifetime (ALT) of more than 1000 h and 2800 h under the ISOS-L2 and ISOS-D3 testing conditions, respectively. Long-term outdoor monitoring of the OPV modules was conducted in a typical central European climate, considering two distinct mounting angles that hold significant relevance for BIPV installations i.e., 45° inclination with respect to the ground (representing the optimal tilt angle of the site) and 90° vertical mounting (as mostly encountered in BIPV façades). The ISOS-O2 protocol was used as the test standard for outdoor monitoring. The results show that the OPV modules can offer higher daily specific energy yields (YFD), i.e., higher ratios of daily energy yield and STC WP capacity of the module, than a reference mono-crystalline (m-Si) module for BIPV installations typical of a rooftop case (i.e., 45°), whereas for façade integrated cases (i.e., 90°), OPV modules offer YFD values identical to that of m-Si modules. Detailed laboratory investigations reveal that the higher YFD values of the OPV modules at 45° mounting stems from their negligible temperature coefficient of −0.008% °C−1, whereas at 90° mounting, the angle-dependent response of the modules plays a crucial role.
CRIS-Team Scopus Importer:2025-02-04

Material Strategies to Accelerate OPV Technology Toward a GW Technology - Brabec, Christoph; Distler, Andreas; Du, Xiaoyan; Egelhaaf, Hans-Joachim; Hauch, Jens; Heumüller, Thomas; Li, Ning (Advanced Energy Materials, 2020)
With the rise of the solar power century, photovoltaic applications and installations will go beyond the traditional green field power plants and enter any aspect of daily life. Organic photovoltaics (OPVs) demonstrate certified cell efficiencies of over 17% and are expected to contribute to versatile applications powered by solar energy, for instance, applications rely on flexibility, transparency, color management, or integrability. In this work, the progress of OPV technology is briefly reviewed and the material strategies to accelerate OPV technology toward a GW era are analyzed. In addition to the exciting efficiency values achieved for small area devices, there are many important criteria deciding the success of OPV technology. By taking into consideration the synthetic complexity of OPV materials and the operational stability of OPV devices, the industrial figure of merit (i-FoM) is proposed as a fast and reliable method to verify the true potential of a novel material. Furthermore, “soft” key performance indicators are introduced, such as toxicity, flexibility, transparency, processing, which require different development strategies to reflect the potential of OPV technology for specific applications.
CRIS-Team Scopus Importer:2020-10-09
Keywords: device operational stability; organic photovoltaics; organic solar modules; synthetic complexity

Morphological and electrical control of fullerene dimerization determines organic photovoltaic stability - Heumüller, Thomas; Mateker, William R.; Distler, Andreas; Fritze, Urs F.; Cheacharoen, Rongrong; Nguyen, William H.; Biele, Markus; Salvador, Michael Filipe; von Delius, Max; Egelhaaf, Hans-Joachim; Mcgehee, Michael D.; Brabec, Christoph (Energy and Environmental Science, 2016)
Fullerene dimerization has been linked to short circuit current (J) losses in organic solar cells comprised of certain polymer-fullerene systems. We investigate several polymer-fullerene systems, which present J loss to varying degrees, in order to determine under which conditions dimerization occurs. By reintroducing dimers into fresh devices, we confirm that the photo-induced dimers are indeed the origin of the J loss. We find that both film morphology and electrical bias affect the photodimerization process and thus the associated loss of J. In plain fullerene films, a higher degree of crystallinity can inhibit the dimerization reaction, as observed by high performance liquid chromatography (HPLC) measurements. In blend films, the amount of dimerization depends on the degree of mixing between polymer and fullerene. For highly mixed systems with very amorphous polymers, no dimerization is observed. In solar cells with pure polymer and fullerene domains, we tune the fullerene morphology from amorphous to crystalline by thermal annealing. Similar to neat fullerene films, we observe improved light stability for devices with crystalline fullerene domains. Changing the operating conditions of the investigated solar cells from V to J also significantly reduces the amount of dimerization-related J loss; HPLC analysis of the active layer shows that more dimers are formed if the cell is held at V instead of J. The effect of bias on dimerization, as well as a clear correlation between PL quenching and reduced dimerization upon addition of small amounts of an amorphous polymer into PC60BM films, suggests a reaction mechanism via excitons.
Keywords: Engineering controlled terms: Amorphous films; Crystalline materials; Dimerization; Dimers; Fullerenes; High performance liquid chromatography; Liquid chromatography; Organic polymers; Polymer films; Polymers Amorphous polymers; Crystalline fullerene; Degree of crystallinity; Dimerization reactions; Electrical control; Operating condition; Organic photovoltaics; Polymer-fullerene system Engineering main heading: Solar cells

On the theoretical framework for meniscus-guided manufacturing of large-area OPV modules - Gumpert, Fabian; Janßen, Annika; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Progress in Organic Coatings, 2024)
For the manufacturing of thin films of solution-processable organic semiconductors, e.g. for organic photovoltaics (OPV), meniscus guided-coating techniques are the method of choice for large-scale industrial applications. However, the process requires an in-depth understanding of the respective fluid dynamics to control the resulting film thickness. In this article, we derive an analytical expression to describe the layer thickness of coatings manufactured with a trapezoidal-shaped applicator as a function of various fluid and process parameters. The analytical calculations are compared with results from computational fluid dynamics (CFD) simulations and experimental data for an industrially relevant OPV active material system. The good agreement of all three approaches demonstrates the potential of the analytical and simulative methods to minimize the number of time- and resource-consuming experiments. Furthermore, our theoretical model can be used to enhance the homogeneity of large-area coatings by means of an acceleration profile of the applicator that can compensate for the liquid loss during the coating process. The respective analytical expression is validated by simulated and experimentally obtained data for long-distance coatings. Finally, this approach is used to fabricate a large-area OPV module with new world record efficiency.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Accelerated coating velocity; Analytical description; Computational fluid dynamics; Meniscus-guided coating; Organic photovoltaics; Thin films

Organic photovoltaic modules with new world record efficiencies - Distler, Andreas; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2020)
During the last years, the development of new active materials has led to constant improvement in the power conversion efficiency (PCE) of solution-processed organic photovoltaics (OPV) to nowadays record values above 17% on small lab cells. In this work, we show the developments and results of a successful upscaling of such highly efficient OPV systems to the module level on large areas, which yielded two new certified world record efficiencies, namely, 12.6% on a module area of 26 cm2 and 11.7% on a module area of 204 cm2. The decisive developments leading to this achievement include the optimization of the module layout as well as the high-resolution short-pulse (nanosecond) laser structuring processes involved in the manufacturing of such modules. By minimizing the inactive areas within the total module area that are used for interconnecting the individual solar cells of the module in series, geometric fill factors of over 95% have been achieved. A production yield of 100% working modules during the manufacturing of these modules and an extremely narrow distribution of the final PCE values underline the excellent process control and reproducibility of the results. The new developments and their implementation into the production process of the record OPV modules are described in detail, along with the challenges that arose during this development. Finally, dark lock-in thermography (DLIT), electroluminescence (EL), and photoluminescence (PL) measurements of the record module are presented.
CRIS-Team Scopus Importer:2020-09-25
Keywords: certified power conversion efficiency (PCE); laser patterning; organic photovoltaics (OPV); solar modules; world record

Overcoming Moisture-Induced Degradation in Organic Solar Cells - Wachsmuth, Josua; Distler, Andreas; Deribew, Dargie; Salvador, Michael Filipe; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Unencapsulated organic solar cells are prone to severe performance losses in the presence of moisture. Accelerated damp heat (85 °C/85% RH) studies are presented and it is shown that the hygroscopic hole-transporting PEDOT:PSS layer is the origin of device failure in the case of prototypical inverted solar cells. Complementary measurements unveil that under these conditions a decreased PEDOT:PSS work function along with areas of reduced electrical contact between active layer and hole-transport layer are the main factors for device degradation rather than a chemical reaction of water with the active layer. Replacements for PEDOT:PSS are explored and it is found that tungsten oxide (WO3) or phosphomolybdic acid (PMA)—materials that can be processed from benign solvents at room temperature—yields comparable performance as PEDOT:PSS and enhances the resilience of solar cells under damp heat. The stability trend follows the order PEDOT:PSS << WO3 < PMA, with PEDOT:PSS-based devices failing after few minutes, while PMA-based devices remain nearly pristine over several hours. PMA is thus proposed as a robust, solution-processable hole extraction layer that can act as a one to one replacement of PEDOT:PSS to achieve organic solar cells with significantly improved longevity.
CRIS-Team Scopus Importer:2023-06-02
Keywords: degradation and stability; humidity; organic photovoltaics; phosphomolybdic acid; solution processed

Over one-micron-thick void-free perovskite layers enable highly efficient and fully printed solar cells - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Distler, Andreas; Li, Chaohui; Forberich, Karen; Tian, Jingjing; Hemasiri, Naveen Harindu; Liu, Chao; Zhang, Jiyun; Yang, Fu; Le Corre, Vincent Marc; et al. (Energy and Environmental Science, 2025)
Commercialization of perovskite photovoltaics hinges on the successful transition from laboratory-scale fabrication to industrial-scale manufacturing. A key challenge in fully printed perovskite solar cells with non-reflecting back electrodes is the deposition of high-quality, over-one-micron-thick perovskite layers to minimize photocurrent losses from incomplete light absorption. However, the formation of voids at the substrate/perovskite interface impedes the fabrication of such layers. Here, phase-field simulations reveal that the bottom voids originate from trapped residual solvents, driven by nanocrystal aggregation at the liquid-vapor interface during drying. Guided by these insights, we introduce a two-dimensional (2D) perovskite layer-assisted growth strategy to promote heterogeneous nucleation at the substrate, accelerating 3D perovskite crystallization and preventing solvent entrapment. This strategy enables the formation of highly crystalline, monolithic perovskite films exceeding one micrometer in thickness. The resulting void-free films maximize photocurrent extraction, achieving power conversion efficiencies of 19.9% on rigid substrates and 17.5% on flexible substrates in fully printed perovskite solar cells with non-reflecting carbon electrodes.
CRIS-Team Scopus Importer:2025-05-30

Photodegradation of Si-PCPDTBT:PCBM active layer for organic solar cells applications: A surface and bulk investigation - Tournebize, Aurelien; Seck, Mamadou; Vincze, Andrej; Distler, Andreas; Egelhaaf, Hans-Joachim; Brabec, Christoph; Rivaton, Agnes; Peisert, Heiko; Chasse, Thomas (Solar Energy Materials and Solar Cells, 2016)
The photooxidation of a polymer blend film used in efficient solar cells based on poly[(4,40-bis(2-ethylhexyl)dithieno[3,2-b:20,30- d]silole)-2,6-diylalt-(2,1,3-benzothiadiazole)-4,7-diyl], (Si-PCPDTBT) and [6,6]-phenyl-C71-butyric acid methyl (PC70BM) has been investigated. A set of experiments from complementary techniques was developed to monitor the modifications during ageing that occur not only in the bulk but also at the surface. The surface analyses were performed by X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM), and the bulk analyses by UV–visible spectroscopy and infrared (IR) spectroscopy. The results reveal that the silicon bridge atom is the first target of degradation. We have identified the existence of a photooxidation profile within the 300 nm thick film. Such a heterogeneous degradation was confirmed by time-of-flight secondary ion mass spectrometry (TOF-SIMS) depth profiling.
Keywords: Active layer; Degradation; Organic solar cell; Photooxidation profile

Predicting layer thicknesses by numerical simulation for meniscus-guided coating of organic photovoltaics - Gumpert, Fabian; Janßen, Annika; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Engineering Applications of Computational Fluid Mechanics, 2023)
To achieve maximum efficiency in organic photovoltaics (OPV), functional layers with uniform and exactly predefined thickness are required. An in-depth understanding of the coating process is therefore crucial for an accurate process control. In this paper, the meniscus-guided blade coating process, which is the most commonly used process for the manufacturing of organic electronics, is investigated by experimental and numerical methods. A computational fluid dynamics (CFD) model is created to simulate the coating behaviour of P3HT:O IDTBR, an industrial state-of-the-art active material system used in OPV, and its results' independence of numerical parameters is ensured. In particular, the influence of the coating velocity and the initially injected fluid volume on the resulting wet film thickness is studied. The developed CFD analysis is able to reproduce the experimental results with very high accuracy. It is found that the film thickness follows a power law dependence on the velocity (˜v 2/3) and a linear dependence on the ink volume (˜V). Accordingly, an analytical expression based on our theoretical considerations is presented, which predicts the wet film thickness as a function of the coating velocity and the ink volume only based on easily accessible ink properties. Consequently, this CFD model can effectively substitute time-consuming and expensive experiments, which currently have to be performed manually in the laboratory for a multitude of novel material systems, and thus supports highly accelerated material research. Moreover, the results of this work can be used to achieve homogeneous large-area coatings by utilising accelerated blade coating.
CRIS-Team Scopus Importer:2023-08-18
Keywords: coating techniques; COMSOL multiphysics; Numerical simulation; organic photovoltaics; renewable energy; thin films

Printing High-Quality Formanidinum Lead Triiodide Films: Understanding the Critical Role of α-Phase Nucleation Before Thermal Annealing - Qiu, Shudi; Dong, Lirong; Jang, Dongju; Yang, Fu; García Cerrillo, José; Li, Chaohui; Xie, Zhiqiang; Luo, Junsheng; Guo, Fei; Distler, Andreas; Du, Tian; Brabec, Christoph; et al. (Advanced Energy Materials, 2024)
Upscaling the coating of formamidinium lead triiodide (FAPbI3) thin film is essential to realizing full printing and thereby roll-to-roll production of perovskite photovoltaics. However, thin-film FAPbI3 processed from antisolvent-free, printing methods suffer from undesirable degradation to the non-photoactive phase, particularly in ambient processing conditions. Here, the most critical stage in thin-film processing is identified as the gas-quenching treatment of the as-cast wet film. It is crucial to achieve both the nucleation of α-phase nanocrystals and their sufficient growth at room temperature, which are indispensable for templating the growth of a highly crystalline and stable α-FAPbI3 film during subsequent thermal annealing. The gas-quenching-treated film without these α-phase nanocrystals can only be converted to meta-stable α-FAPbI3 by thermal annealing. By precisely identifying the spontaneous doping of cesium ion (Cs+) as a key factor in triggering α-FAPbI3 nucleation and the role of chloride ion (Cl−) in enhancing nanocrystal growth, a generalized mechanism for additive engineering for the precursor ink is theorized. The identified mechanism translates to a power conversion efficiency of 19.36% for fully printed carbon-electrode solar cells, 16.23% for carbon-electrode minimodules, and excellent operational stability, showing the promising potential of this proposed fabrication route in the upscaling of perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: carbon-electrode; cesium ion; FAPbI; nucleation; perovskite photovoltaics

Renewed Prospects for Organic Photovoltaics - Zhang, Guichuan; Lin, Francis R.; Qi, Feng; Heumüller, Thomas; Distler, Andreas; Egelhaaf, Hans-Joachim; Li, Ning; Chow, Philip C. Y.; Brabec, Christoph; Jen, Alex K. -Y.; Yip, Hin-Lap (Chemical Reviews, 2022)
Organic photovoltaics (OPVs) have progressed steadily through three stages of photoactive materials development: (i) use of poly(3-hexylthiophene) and fullerene-based acceptors (FAs) for optimizing bulk heterojunctions; (ii) development of new donors to better match with FAs; (iii) development of non-fullerene acceptors (NFAs). The development and application of NFAs with an A-D-A configuration (where A = acceptor and D = donor) has enabled devices to have efficient charge generation and small energy losses (Eloss < 0.6 eV), resulting in substantially higher power conversion efficiencies (PCEs) than FA-based devices. The discovery of Y6-type acceptors (Y6 = 2,2'-((2Z,2'Z)-((12,13-bis (2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]-thiadiazolo [3,4-e]-thieno- [2 ",3 ":4',5']thieno-[2',3':4,5]pyrrolo-[3,2-g]thieno-[2',3':4,5]thieno-[3,2-b]indole-2,10- diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))-dimalononitrile) with an A-DA' D-A configuration has further propelled the PCEs to go beyond 15% due to smaller Eloss values (& SIM;0.5 eV) and higher external quantum efficiencies. Subsequently, the PCEs of Y6-series single-junction devices have increased to > 19% and may soon approach 20%. This review provides an update of recent progress of OPV in the following aspects: developments of novel NFAs and donors, understanding of the structure-property relationships and underlying mechanisms of state-of-the-art OPVs, and tasks underpinning the commercialization of OPVs, such as device stability, module development, potential applications, and high-throughput manufacturing. Finally, an outlook and prospects section summarizes the remaining challenges for the further development of OPV technology.
CRIS-Team WoS Importer:2022-08-26

Semitransparent Organic Photovoltaic Devices: Interface/Bulk Properties and Stability Issues - Paci, Barbara; Righi Riva, Flavia; Generosi, Amanda; Guaragno, Marco; Mangiacapre, Emanuela; Brutti, Sergio; Wagner, Michael; Distler, Andreas; Egelhaaf, Hans Joachim (Nanomaterials, 2024)
In the present work, an insight on the morpho/structural properties of semitransparent organic devices for buildings’ integrated photovoltaics is presented, and issues related to interface and bulk stability are addressed. The organic photovoltaic (OPV) cells under investigation are characterized by a blend of PM6:Y6 as a photo-active layer, a ZnO ETL (electron transporting layer), a HTL (hole transporting layer) of HTL-X and a transparent electrode composed by Ag nanowires (AgNWs). The devices’ active nanomaterials, processed as thin films, and their mutual nanoscale interfaces are investigated by a combination of in situ Energy Dispersive X-ray Reflectometry (EDXR) and ex situ Atomic Force Microscopy (AFM), X-ray Diffraction (XRD) and micro-Raman spectroscopy. In order to discriminate among diverse concomitant aging pathways potentially occurring upon working conditions, the effects of different stress factors were investigated: light and temperature. Evidence is gained of an essential structural stability, although an increased roughness at the ZnO/PM6:Y6 interface is deduced by EDXR measurements. On the contrary, an overall stability of the system subjected to thermal stress in the dark was observed, which is a clear indication of the photo-induced origin of the observed degradation phenomenon. Micro-Raman spectroscopy brings light on the origin of such effect, evidencing a photo-oxidation process of the active material in the device, using hygroscopic organic HTL, during continuous illumination in ambient moisture conditions. The process may be also triggered by a photocatalytic role of the ZnO layer. Therefore, an alternative configuration is proposed, where the hygroscopic HTL-X is replaced by the inorganic compound MoOx. The results show that such alternative configuration is stable under light stress (solar simulator), suggesting that the use of Molybdenum Oxide, limiting the photo-oxidation of the bulk PM6:Y6 active material, can prevent the cell from degradation.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Ag nanowires; in-situ characterization; interfaces; morphology; OPVs; structural properties

Silver Electrodes for Organic Solar Cells Printed via Laser-Induced Forward Transfer - Bibrack, Max; Distler, Andreas; Wagner, Michael; Forberich, Karen; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy Technology, 2025)
Laser-induced forward transfer (LIFT) is presented as a new, contactless, and roll-to-roll compatible method for the deposition of silver top electrodes for organic solar cells (OSCs). Employing a nanosecond laser, highly reflective silver electrodes are printed by LIFT onto OSCs with P3HT:o-IDTBR bulk heterojunction layers. Upon optimization of ink composition, source film thickness, and laser parameters, the resulting organic solar cells reach efficiencies of more than 5%, which are similar to those of reference devices with vapor-deposited silver electrodes.
CRIS-Team Scopus Importer:2025-02-04
Keywords: laser-induced forward transfer process; nanosecond laser; organic photovoltaics; printable electrodes; silver nanoparticles

Solution-coated barriers for organic electronics - Channa, Iftikhar Ahmed; Distler, Andreas; Brabec, Christoph; Egelhaaf, Hans-Joachim (Organic Flexible Electronics, 2021)
This chapter provides a review on solution processed barriers for flexible organic electronics. After elaborating on the necessity for encapsulation of organic devices by describing the degradation mechanisms caused by oxygen and water, the state of the art of vacuum-deposited barriers is briefly addressed as it presently defines the benchmark of barrier technology. Subsequently, the fundamentals of permeation of gases through barriers and the characterization methods for barrier performance are described. The main part of the chapter gives an overview of the material systems used for manufacturing solution-processed barriers. We start with the methods relying on reducing diffusion and solubility coefficients of oxygen and water in barrier films. Subsequently, barriers based on tortuosity and barriers based on covering substrates with layers of zero or very low permeability are described. Finally, the role of getters is elucidated. The chapter is concluded with highlighting some of the present challenges in the field of solution processed flexible barriers.<br
Keywords: Flexible barriers; flexible electronics; flexible packaging; organic photovoltaics; organic light emitting diodes; OLED; OPV; OFET; device lifetime; accelerated ageing

The 2021 flexible and printed electronics roadmap - Bonnassieux, Yvan; Brabec, Christoph; Cao, Yong; Carmichael, Tricia Breen; Chabinyc, Michael L.; Cheng, Kwang Ting; Cho, Gyoujin; Chung, Anjung; Cobb, Corie L.; Distler, Andreas; Egelhaaf, Hans-Joachim; Grau, Gerd; et al. (Flexible and Printed Electronics, 2021)
This roadmap includes the perspectives and visions of leading researchers in the key areas of flexible and printable electronics. The covered topics are broadly organized by the device technologies (sections 1–9), fabrication techniques (sections 10–12), and design and modeling approaches (sections 13 and 14) essential to the future development of new applications leveraging flexible electronics (FE). The interdisciplinary nature of this field involves everything from fundamental scientific discoveries to engineering challenges; from design and synthesis of new materials via novel device design to modelling and digital manufacturing of integrated systems. As such, this roadmap aims to serve as a resource on the current status and future challenges in the areas covered by the roadmap and to highlight the breadth and wide-ranging opportunities made available by FE technologies.
CRIS-Team Scopus Importer:2021-06-25
Keywords: E-textiles; Flexible and printed electronics; Organic light emitting diodes; Organic photovoltaics; Roll-to-roll printing; Sensors; Thin film transistors

The Effect of PCBM Dimerization on the Performance of Bulk Heterojunction Solar Cells - Distler, Andreas; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Rodman, Sheila; Waller, Dave; Cheon, Kap-Soo; Lee, Mike; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
Increasing the lifetime of polymer based organic solar cells is still a major challenge. Here, the photostability of bulk heterojunction solar cells based on the polymer poly[4,4'-bis(2-ethylhexyl)dithieno[3,2-b:2',3'-d]silole)-2,6-diyl-alt-[2,5-bis(3-tetradecylthiophen-2-yl)thiazole[5,4-d]thiazole)-1,8-diyl] (PDTSTzTz) and the fullerene [6,6]-phenyl-C-butyric acid methyl ester (PCBM) under inert atmosphere is investigated. Correlation of electrical measurements on complete devices and UV-vis absorption measurements as well as high-performance liquid chromatography (HPLC) analysis on the active materials reveals that photodimerization of PCBM is responsible for the observed degradation. Simulation of the electrical device parameters shows that this dimerization results in a significant reduction of the charge carrier mobility. Both the dimerization and the associated device performance loss turn out to be reversible upon annealing. BisPCBM, the bis-substituted analog of PCBM, is shown to be resistant towards light exposure, which in turn enables the manufacture of photostable PDTSTzTz:bisPCBM solar cells. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei

Thin Film Encapsulation of Organic Solar Cells by Direct Deposition of Polysilazanes from Solution - Channa, Iftikhar Ahmed; Distler, Andreas; Zaiser, Michael; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2019)
Organic electronic devices (OEDs), e.g., organic solar cells, degrade quickly in the presence of ambient gases, such as water vapor and oxygen. Thus, in order to extend the lifetime of flexible OEDs, they have to be protected by encapsulation. A solution-based encapsulation method is developed, which allows the direct deposition of the diffusion barrier on top of OEDs, thus avoiding lamination of barrier films. The method is based on the deposition of a perhydropolysilazane (PHPS) ink and its subsequent conversion into a silica layer by deep UV irradiation. The resulting barrier films show water vapor transmission rates (WVTRs) of <10(-2) g m(-2) d(-1) (40 degrees C/85% relative humidity (RH)) and oxygen transmission rates (OTRs) of <10(-2) cm(3) m(-2) d(-1) bar(-1) at ambient conditions. Flexibility of the resulting barrier films is improved by coating a barrier stack of several thin PHPS layers alternating with organic polymer interlayers. These stacks show an increase of WVTR values by less than 10% after 3000 bending cycles. Direct coating of the PHPS films on top of organic solar cells enhances the device lifetime in damp heat conditions from a few hours to beyond 300 h.
CRIS-Team WoS Importer:2019-08-09

Upscaling Solution-Processed Perovskite Photovoltaics - Yang, Fu; Jang, Dongju; Dong, Lirong; Qiu, Shudi; Distler, Andreas; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
The performance of hybrid organic–inorganic perovskite solar cells has reached a certified efficiency of 25.5% over the past decade, which has attracted significant attention as a promising candidate for photovoltaic (PV) applications. However, the most efficient perovskite solar cells were produced by the technique of spin coating, which is extremely limited in terms of upscaling production for the commercialization of the technology. Furthermore, the efficiencies of large-area perovskite modules are still significantly lower than those of lab size solar cells. Thus, there are still some challenges that need to be overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The first challenge lies in preparing high-quality perovskite layers by low-cost and scalable techniques with high reproducibility. Second, selecting and depositing charge extraction layers as well as bottom and top electrodes by scalable and low-cost techniques are essential tasks. In this review, recent progress and challenges of scalable technologies for solution-based coating and printing of perovskite PVs are summarized and analyzed. Based on the analysis, strategies and opportunities are proposed to promote the development of stable and efficient large-area perovskite PV toward commercialization.
CRIS-Team Scopus Importer:2021-10-22
Keywords: high-efficiency; long-term stability; perovskite photovoltaics; roll-to-roll production; scalable coating